(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The prevalence of chronic kidney diseases and renal failure varies across regions and remains a serious and pressing issue in the field of public health. It is noteworthy that the clinical manifestation of chronic renal failure typically develops only after the loss of 70–75% of functional nephrons. As the condition progresses, the number of remaining nephrons continues to decline. The etiological factors underlying this pathology are highly diverse. They include congenital anomalies (for example, polycystic kidney disease, hydronephrosis, and renal hypoplasia) as well as acquired or unidentified inflammatory diseases (such as pyelonephritis and glomerulonephritis), drug-induced nephropathies (for instance, those caused by medications or amino acids), infections, metabolic disorders (such as diabetes mellitus), autoimmune diseases, and others [1,2].